2014
DOI: 10.1111/ddi.12230
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and resilience: can the abrupt end of extreme drought reverse avifaunal collapse?

Abstract: Aim Climate change is expected to increase the frequency and intensity of extreme climatic events, such as severe droughts and intense rainfall periods. We explored how the avifauna of a highly modified region responded to a 13year drought (the 'Big Dry'), followed by a two-year period of substantially higher than average rainfall (the 'Big Wet').Location Temperate woodlands in north central Victoria, Australia.Methods We used two spatially extensive, long-term survey programmes, each of which was repeated thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 60 publications
2
72
0
Order By: Relevance
“…When an ecological unit -for example an ecological community -experiences periodic disturbance (e.g., frequent fires, recurrent hurricanes), it might show a gradual but long-term shift in community structure, such as loss of species [51]. Such change is particularly likely when a community is subject to multiple disturbances that interact at different temporal scales, for example when drought events (multi-year) occur in fragmented landscapes (subject to decades or centuries of disturbance).…”
Section: Insights Into Long-term Change In Biodiversitymentioning
confidence: 99%
“…When an ecological unit -for example an ecological community -experiences periodic disturbance (e.g., frequent fires, recurrent hurricanes), it might show a gradual but long-term shift in community structure, such as loss of species [51]. Such change is particularly likely when a community is subject to multiple disturbances that interact at different temporal scales, for example when drought events (multi-year) occur in fragmented landscapes (subject to decades or centuries of disturbance).…”
Section: Insights Into Long-term Change In Biodiversitymentioning
confidence: 99%
“…Continuous measurements of vegetation throughout the drought were not made so that we are only able to make a direct comparison between the changes in avifauna and the vegetation for the two time periods; early in and after the Big Dry. However, we are confident of the consistency of the changes in the avifauna because these were monitored frequently throughout the Big Dry (Mac Nally et al 2009;Bennett et al 2014b). Reductions in canopy foliage, ground-litter and shrub cover during the Big Dry (Bennett et al 2013) was likely to reduce the availability of both nest-sites and food.…”
Section: Discussionmentioning
confidence: 90%
“…Species were allocated to a single guild, deemed most appropriate. For a full explanation of the selected guilds see (Bennett et al 2014b). …”
Section: Bird Surveysmentioning
confidence: 99%
See 1 more Smart Citation
“…While a nomad and an equivalent sedentary species could be at equally high risk from threats whilst occupying a bottleneck or refugial site, the ability of nomads to expand in distribution (and population) when environmental conditions improve may buffer them from stochastic threats over the long term as they can move on and take advantage of good conditions elsewhere (Dean 2004). However, recent work has found that the buffering effect of movements is obviated in the face of widespread habitat loss, with equal declines among migrants and non-migrants (Albright et al 2010;Bennett et al 2014). Movement itself could be risky in the sense that locations and timings of suitable resources are unpredictable and irregular (MacNally 2009).…”
Section: Discussionmentioning
confidence: 99%